POLA ASUH ORANG TUA MILENIAL DALAM MENDIDIK ANAK GENERASI ALPHA DI ERA TRANSFORMASI DIGITAL - Halen Dwistia; Muhammad Iqbal; Sodikin Sodikin; Sukaris Munandar (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This study aims to analyze the parenting styles of millennial parents in educating Generation Alpha children in the digital transformation era. The raised issues include challenges faced by parents in utilizing technology and its impact on child development. Qualitative Approach with Literature Analysis. The results show that millennial parents tend to apply authoritative and democratic parenting styles while providing strict supervision of technology use to prevent gadget addiction. The conclusion emphasizes that appropriate parenting styles can facilitate positive child development in a digital environment. Recommendations for parents include prioritizing social interaction and educational values, as well as wisely utilizing technology.